An investigation into pragmatic features of making apology in English and Vietnamese - Nguyễn,Thị Nguyệt (2015)
Based on theoretical background of pragmatics, this study attempts to investigate similarities and differences in making apology (MA) between English native speakers (ENSs) and Vietnamese native speakers(VNSs) using a modified version of the discourse completion task (DCT) developed by Beebe at al.(1990). Fifty ENSs (22 males and 28 females) and fifty VNSs (16 males and 34 females) participated in the study, resulting in 2,374 utterances of MA. The data were analyzed using Excel software to compare the frequency off MA in selected situations. It was found that the frequency of use of MA by ENSs is different from that by VNNs, though they do share some similarities. The study pays special attention to the choice of frequency of apology strategies as well as those of direct - indirect strategies. The results suggest that the awareness of culture gaps should be raised in English teaching and learning in Vietnam.